2014
DOI: 10.1134/s0021364014040079
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-containing species in the structure of the synthesized nano-hydroxyapatite

Abstract: Synthesized by the wet chemical precipitation technique hydroxyapatite powders (HAp) with the sizes of the crystallites of (20-10 50) nm and 1 m were analyzed by multi-frequency (9 and 95 GHz) electron paramagnetic resonance (EPR) methods. It is shown that during the synthesis process nitrate anions from the reagents (by-products) could incorporate into the HAp structure. The relaxation times and EPR parameters of the axially symmetric NO 3 2paramagnetic centers detected after X-ray irradiation of the product… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…The sharp band associated to the ν 3 NO 3 asymmetric stretching at 1,384 cm −1 in N 0.3 -ACP confirms the material functionalization. The relative intensities of the ν 3 NO 3 bands in N 0.3 -ACP and N 0.3 -nAp, and the nitrate content by elemental analysis (2.12 and 0.44 w%, respectively, Table S2 ) indicate that longer maturation times, favouring self-healing processes, limit nitrate functionalization, in line with previous reports 23 , 39 , 40 . This result, and plant tests presented elsewhere 23 , suggest that fully amorphous NPs are best candidates for application as N-based nanofertilizers.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The sharp band associated to the ν 3 NO 3 asymmetric stretching at 1,384 cm −1 in N 0.3 -ACP confirms the material functionalization. The relative intensities of the ν 3 NO 3 bands in N 0.3 -ACP and N 0.3 -nAp, and the nitrate content by elemental analysis (2.12 and 0.44 w%, respectively, Table S2 ) indicate that longer maturation times, favouring self-healing processes, limit nitrate functionalization, in line with previous reports 23 , 39 , 40 . This result, and plant tests presented elsewhere 23 , suggest that fully amorphous NPs are best candidates for application as N-based nanofertilizers.…”
Section: Resultssupporting
confidence: 90%
“…ions, their incorporation in apatite has been demonstrated by previous experimental and computational studies 39,40 . However, specific effects on the crystal lattice have not been reported, likely due to experimental difficulties in detecting tiny shifts of broad Bragg peaks by conventional XRPD.…”
Section: Lattice Variations By Nomentioning
confidence: 70%
See 2 more Smart Citations
“…2 shows the ESE detected EPR spectrum of the NO 3 2radiation induced radicals due to the hyperfine interaction between the stable nitrogencontaining paramagnetic center with electronic spin with S = ½ and one nitrogen nuclear spin with I = 1 for 14 N isotope. From the previous EPR data analysis it was concluded that NO 3 2radiation induced radical substitutes PO 4 3position in the HAp structure while the carbonate ions could also replace OH group [15][16][17][18]. The T 1e measurements were done in the magnetic field B 0 = 343 mT (see Fig.…”
Section: Resultsmentioning
confidence: 99%